Perbedaan Status Gizi dan Malnutrisi Mikronutrien pada Anak Sekolah Dasar Usia 8–13 Tahun di Bogor, Indonesia: Differences in the Nutritional and Micronutrient Malnutrition Status Among Primary School Children Aged 8–13 Years in Bogor, Indonesia - Al Khairiyah, Hanifah; Hardinsyah, Hardinsyah; Dewi, Mira; Alamsyah, Putri Rahmah; Riawan, Agus (Universitas Airlangga, 2025)
Background: Indonesia is experiencing a triple burden of malnutrition, defined as the coexistence of undernutrition, overnutrition, and micronutrient deficiencies. The majority of previous research has focused on the first 1000 days of life, while studies on school-age children remain limited, despite this developmental period being crucial for determining future health and well-being. Objectives: The objective of this study is to analyze the prevalence of undernutrition, overnutrition, and micronutrient deficiencies among primary school children in Bogor, Indonesia. Methods: This cross-sectional study included 915 fourth- and fifth-grade students who were selected for inclusion. The collected data encompassed individual characteristics, family socioeconomic status, anthropometric measurements (actual body weight, height, and skinfold thickness), and blood biomarkers. Nutritional status was assessed using BMI-for-age (BMI/A), body fat percentage (Slaughter equation), hemoglobin levels (non-cyanide method), and serum concentrations of vitamin A and B12 (Liquid Chromatography and Mass Spectrometry, LCMS). Results: The prevalence of chronic energy deficiency was 2.4%, overnutrition (overweight and obesity) was 12.4%, and high body fat was 12.8%. Micronutrient deficiencies were prevalent, with 40.1% of subjects experiencing anemia, 18.6% exhibiting vitamin A deficiency, and 52.2% demonstrating vitamin B12 deficiency. No statistically significant differences were found in nutritional status between boys and girls, as measured by BMI/A and blood biomarkers. However, girls had significantly higher body fat percentages (p-value<0.001). Conclusions: The prevalence of micronutrient deficiencies was found to exceed that of both undernutrition and overnutrition. Further research is needed to explore the underlying factors contributing to these nutritional issues, considering various covariates. Targeted and specific interventions are critical in order to prevent and address the triple burden of malnutrition among primary school children in Bogor, Indonesia.